Characterization of precipitation and recharge in the peripheral aquifer of the Salar de Atacama - Valdivielso, Sonia; Vázquez-Suñé, Enric; Herrera, Christian; Custodio, Emilio (Science of The Total Environment, 2022)
To reduce uncertainty in the identification of the recharge areas in the Peripheral Aquifer of the Salar de Atacama (SdA), a few studies have investigated the isotopic characteristics and moisture sources of precipitation in the SdA basin. In the present study, the seasonal cycle of meteorological parameters and the relationships of this cycle with sea surface temperature anomalies are shown, the sources of humidity are identified, and the types of clouds producing precipitation are defined. Finally, the isotopic compositions of precipitation, surface water and groundwater in the SdA basin and the Altiplano-Puna Plateau basins are analysed to identify the area recharging the northern, eastern and southern subbasins of the SdA. In summer, when the highest temperature, relative humidity and precipitation values of the year are recorded, the precipitation is due to deep convection. The trajectories of the arriving air masses can be classified into three groups: from the North Atlantic Ocean across the Amazon basin, from the South Atlantic Ocean across the La Plata River basin and the Gran Chaco, and from the Pacific Ocean. In winter, when the temperature, relative humidity and precipitation are lower, the moisture masses come from the Pacific Ocean. Winter precipitation is more depleted in heavy isotopes than summer precipitation. The isotopic analysis of precipitation, surface water and groundwater shows that recharge of the eastern subbasins of the SdA occurs by diffuse infiltration of precipitation and concentrated infiltration of surface water, both within the hydrographic basin of the SdA. The meteoric source of the waters in the Altiplano-Puna Plateau basins is isotopically lighter than the waters found in the side basins of the SdA, so there is no significant water quantity transfer to the peripheral aquifers of the SdA from outside the hydrographic basin. The authors thank SQM (Chile) for their support and cooperation, Atacama Large Millimeter/submillimeter Array (ALMA), to the staff of the Paso Jama ...